A Comparative Study of Stroke Outcomes in Patients Receiving Edaravone and Citicoline - Sadi, Aleena Muhammed; Maitheen, Khadeeja; Periera, Laveena Joykutty; John, Cijy; Ramachandran, Lakshmi; Chandrasekharan, Soumya V (Indian Journal of Pharmacy Practice)
Background: The effectiveness of Edaravone and Citicoline combination therapy in adult stroke patients has not yet been the subject of a focused investigation. Given this research gap, it is crucial to direct our attention towards investigating the potential neuroprotective benefits of Citicoline and Edaravone. The aim of this study was to assess the effect of Edaravone and Citicoline in stroke outcomes. Materials and Methods: All patients older than 18 years old, were admitted to the Neurology Department within 72 hr for this investigation. Group A consisted of stroke patients of any severity who got Edaravone and Citicoline in addition to standard stroke care; Group B consisted of stroke patients of the same severity who did not get these drugs in addition to standard stroke care. The National Institute of Health Stroke Scale (NIHSS) was used to quantify stroke severity at admission and discharge and the Modified Rankin Scale (MRS) was used to measure stroke outcomes at admission, discharge, the first month and the third month after a stroke. The Chi-Square test was employed for analysis to ascertain whether the results of strokes differed significantly from one another. A significant P value of more than 0.05 was assigned. Results: After the application of NIHSS Scale, at discharge there were 8 patients in Group A with moderate stroke severity, 22 with minor stroke severity and none with moderate to severe. In Group B, 22 patients had a mild stroke and 7 had a moderate stroke and one had a moderate to severe stroke. There was no discernible variation in the severity of strokes between the groups according to the NIHSS assessment. Mean MRS scores at discharge, 1st month and 3rd month were lowest in Group A (p=0.024, 0.011 and 0.02 respectively) which shows a better outcome in this group. Conclusion: The combination of neuroprotectant therapy using Edaravone and Citicoline is found to have positive impact on stroke outcomes in the study population.
Keywords: Citicoline; Edaravone; MRS; NIHSS; Stroke